2003
DOI: 10.1152/physiolgenomics.00086.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gene expression profile in tolerizing murine cardiac allograft by costimulatory blockade

Abstract: The induction of specific tolerance would be the ultimate achievement in transplant immunology, but the precise mechanisms of immunologic tolerance remain largely unknown. Here, we investigated global gene expression analysis in tolerizing murine cardiac allografts by means of oligonucleotide microarrays. Tolerance induction was achieved in cardiac allografts from BALB/c to C57BL/6 mice by daily intraperitoneal injection of anti-CD80 and anti-CD86 monoclonal antibodies (mAbs). Comparative analysis revealed 64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…We showed that tolerated allografts exhibit strong infiltration and a marked expression of a number of genes for molecules usually considered as pro-inflammatory factors (including chemokines, cytokines, and cytotoxicity-or activation-related genes). High expres- sion of these "proinflammatory" genes may therefore not be necessarily considered as predictive or as diagnosis of graft failure (28). Expression of these genes in tolerated allografts could reflect the presence of both effector cells and regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that tolerated allografts exhibit strong infiltration and a marked expression of a number of genes for molecules usually considered as pro-inflammatory factors (including chemokines, cytokines, and cytotoxicity-or activation-related genes). High expres- sion of these "proinflammatory" genes may therefore not be necessarily considered as predictive or as diagnosis of graft failure (28). Expression of these genes in tolerated allografts could reflect the presence of both effector cells and regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…A set of genes (TGF-ß2, ppENK, GM2a, GITR, IL-1R2) were identified by SAGE screening that are specifically upregulated in regulatory T cells associated with tolerance of skin allografts (41,42). Matsui et al identified two genes (H2-Ea, Frzb), which are highly expressed in long-term surviving heart allografts (43). In this model long-term survival was induced by costimulatory blockade.…”
Section: Marker For Monitoring Of T-cell Modulating Therapiesmentioning
confidence: 99%
“…Analyses of the gene expression profile changes of an experimental immunosuppressant on rat kidney allografts (63), anti-CD80 and anti-CD86 antibodies on mouse cardiac allografts (64), and anti-CD40 and anti-LFA antibodies (65) on mouse tracheal allografts have been tested to explore gene expression changes associated with attenuation of rejection in these models. A group of chemokine genes was found to be up-regulated in IFN-␥-knockout cardiac recipient mice compared with wild-type mice (66), and a set of genes was associated with IFN regulatory factor-1-deficient mouse cardiac recipients (67).…”
Section: Microarray Gene Expression Analysis Of Nonhuman Transplant Mmentioning
confidence: 99%